PENILAIAN JUMLAH PENGGUNAAN TRUK ANGKUTAN DI DUA PERUSAHAAN HUTAN DI SUMATERA BARAT - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1990)
A  study   on  the productivity  of  logging trucks  at  two  forest  companies  was done  in 1984, and  the result  is reported in  this article. Four logging  trucks  used by PT Ragusa  and  five by PT Pasar Besar were selected  randomly to study transport time and load  volumes  through work  time  study. The  purpose is to find out the optimum number of  trucks  suitable to transport logs from the forests to log ponds, processing places or other  distribution  point.  The result shows  that:Isuzu  TWD 20 trucks  were used to transport  logs at the  two forest  companies.The average log volume  per  and  trip  transportation at PT  Ragusa and PT Pasar Besar were  15.20 m3 and 12.84  m3, respectively.Average productivity at PT Ragusa and PT Pasar Besar were 45.6 m3/day  and 25.68  m3/day, respectively.Logging truck productivities were possibly influenced by load volumes and transport  distance.The  number of  logging  trucks  actually urged  in  hauling  logs at PT  Ragusa and  PT Pasar Besar were  5 and 11 units, respectively. Procurement of  new or reparation  of  idle  logging trucks  is strongly recommended.